2014
DOI: 10.1016/j.infbeh.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

How does non-nutritive sucking support infant feeding?

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link ABSTRACTFifty nine premature infants participated in a randomized controlled study to determine the effectiveness of nonnutritive sucking (NNS). It was predicted that NNS would not accelerate the development of full oral feeding or early language skills as sometimes perceived in practice. However, it was predicted that using NNS as a strategy to support parents to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 28 publications
1
11
0
2
Order By: Relevance
“…Although no significant difference was observed between the groups, neonates in the intervention group attained oral feeding very sooner than the controls. In addition, a greater number of neonates were on breastfeeding in the intervention groups than control group at discharge (33).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although no significant difference was observed between the groups, neonates in the intervention group attained oral feeding very sooner than the controls. In addition, a greater number of neonates were on breastfeeding in the intervention groups than control group at discharge (33).…”
Section: Discussionmentioning
confidence: 91%
“…According to Lessen (2012), the mean length of hospital stay was 41.8 and 44.4 days in the intervention and control groups, respectively, indicating no statistically significant difference between the groups (P = 0.541) (24). Harding et al (2014) showed a significant difference in the length of hospital stay between two intervention groups and the control group (group 1: 21.74 days; group 2: 31 days; group 3: 36.85 days) (P = 0.022) (33). Kamhawy et al (2014) showed that the intervention neonates were discharged at lower corrected age (36.7 weeks versus 37.3 weeks) (31).…”
Section: Discussionmentioning
confidence: 99%
“…In the initial phase non-nutritive sucking (on a pacifier) to stimulate sucking and prepare for nutritive sucking is provided [33]. However, it should be noted that non-nutritive sucking does not always enable an infant to achieve full oral feeding more quickly than those infants who do not use non-nutritive sucking [34]. Using non-nutritive sucking is important for helping the infant to achieve the quiet alert state appropriate for feeding, and it can support parent learning on how to interpret differing infant states and therefore support parent-bonding [34].…”
Section: Active and Passive Oral Motor Exercisesmentioning
confidence: 99%
“…La estimulación orokinésica perioral ayuda a una transición más rápida de sonda a oral. Los niños con más dificultades para adquirir succión madura son los prematuros menores de 28 semanas, los con DBP y los con RCIU, por lo que el trabajo de estimulación debe ser persistente en estos casos 63 . Nutrición intrahospitalaria del prematuro 13…”
Section: Aspectos Adicionales Del Manejo Nutricionalunclassified